Plataforma Schoology y su incidencia en el proceso de enseñanza – aprendizaje en los estudiantes del bachillerato unificado de la Unidad Educativa Prócer José de Antepara del cantón Vinces - Contreras Santillan, Edison Francisco (2019)
The main objective of this research project is to “identify how the use of the schoology platform affects the teaching-learning process in the students of the unified baccalaureate of the“ hero José de Antepara ”educational unit of Vinces canton. To identify the impact that teaching resources have on the teaching-learning process, the application of applied research was used, based on inductive - deductive and analytical methods, developing research techniques, surveys, interviews and direct observation of the entire Population under study, which was made up of 90 students and 8 teachers of the first a and first b of the unified baccalaureate. Through the development and application of the various research methods and strategies, it was possible to verify that the use of teaching resources in the teaching-learning process would contribute to improving the academic performance of the students, since the current educational system requires the implementation of the use of ICTs in the development of classes, to achieve in this way that students develop various skills and also because these types of resources stimulate student interest and motivation in students, thus achieving that they acquire an active, meaningful learning that can be used to put it into practice in everyday situations.